Can daily meteorological measurement of near-surface wind detect climate changes in the Sahel (SE Niger, 1950–1992)?. (January 2016) - Hassane, Bouba; Durand, Alain; Garba, Zibo; Dieppois, Bastien; Sebag, David; Rajot, Jean-Louis; Diedhiou, Arona; Ngounou Ngatcha, Benjamin; Traore, Abdoulkarim
Abstract: Using three daily measurements of wind speed and direction from synoptic weather station data in SE Niger, we examined the diurnal, seasonal and interannual time-scale of Sahel climate variability between 1950 and 1992. The seasonal wind patterns are closely related to the temperatures and West African monsoon dynamics. The transitions between the two seasons are marked by an important increase in calms (wind speed < 0.5 m s −1 ). Such variations are related to meridional shifts of the Inter Tropical Discontinuity (ITD) and Inter Tropical Convergence Zone (ITCZ). Interannual fluctuations of annual wind speeds are consistent with Sahel rainfall variability. Dry years, such as in 1969–1973 and 1983–1986 periods, are associated with negative anomalies in wind speeds mainly due to an increase in calms and dry conditions. Nevertheless, we note several differences: the first period is associated with a yearly increase in the annual mean speed, while the second is associated with a decrease. Differences could be related to changes in atmospheric circulation, especially regarding the strength and latitudinal position of Tropical and African Easterly jets. Highlights: We examine wind speed and direction record to explain Sahelian climate characteristic. We examine the daily variability according to thermal turbulence. Seasonal wind variability is closely related to ITD and ITCZ shifts. The year to year fluctuations are consistent with Sahelian rainfall variability. Dry years showed a possible relationship with the proportion of calm.